2021
DOI: 10.1101/2021.11.23.469742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Basis of Antibiotic Self-Resistance in a Bee Larvae Pathogen

Abstract: Paenibacillus larvae, the causative agent of the devastating honey-bee disease American Foulbrood, produces the cationic polyketide-peptide hybrid paenilamicin that displays high antibacterial and antifungal activity. Its biosynthetic gene cluster contains a gene coding for the N-acetyltransferase PamZ. We show that PamZ acts as self-resistance factor in P. larvae by deactivation of paenilamicin. Using tandem MS, NMR spectroscopy and synthetic diastereomers, we identified the N-terminal amino group of the agma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…We further concluded that the (6 R )-configuration of the terminal amino group in Aga plays a functional role, which is more important for exerting antifungal rather than for antibacterial activity. In our parallel study, we show that the self-resistance factor PamZ acetylates the 6-amino group of Aga and thereby inactivates paenilamicins. Moreover, this study demonstrated that PamZ requires the correct (6 R )-configuration of Aga, being unable to convert the non-native diastereomers PamB2_1 and PamB2_2 .…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…We further concluded that the (6 R )-configuration of the terminal amino group in Aga plays a functional role, which is more important for exerting antifungal rather than for antibacterial activity. In our parallel study, we show that the self-resistance factor PamZ acetylates the 6-amino group of Aga and thereby inactivates paenilamicins. Moreover, this study demonstrated that PamZ requires the correct (6 R )-configuration of Aga, being unable to convert the non-native diastereomers PamB2_1 and PamB2_2 .…”
Section: Resultsmentioning
confidence: 70%
“…This rather small difference in inhibitory potency toward the Gram-negative E. coli ribosome fairly reflected the reasonable conservation of anti-Gram-positive activity despite the non-native 6 S -configuration of Aga in PamB2_2 (Table ). Again, the functional importance of the N-terminal residue Aga was much more evident given the approximately 100-fold weaker ribosome inhibition, when its 6-amino group became N -acetylated ( N -acetyl- PamB2_3 , IC 50 ∼31.9 μM) by PamZ (Figure b; see the Supporting Information for results of the in vitro activation assay of PamZ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1b), a compound originally isolated from a soil sample from New Guinea in the 1970's 6 . A recent structural revision of PamB2 revealed that the (6R)-configuration of the terminal amino group in Agm is important for maximal activity and plays a role in self-resistance, being required for acetylation, and thereby inactivation, by the self-resistance factor PamZ 4,7 . The protection of the N-terminus during biosynthesis by attachment of an Acyl-D-Asn moiety is also a prominent prodrug resistance mechanism 8 .…”
Section: Introductionmentioning
confidence: 99%